Gender, class and space in the field of parenthood: comparing middle‐class fractions in Amsterdam and London. Issue 2 (16th December 2014) - Boterman, Willem R; Bridge, Gary
Abstract : This paper argues that becoming a parent/carer can be seen as a new field of social relations and suggests how gender is the key mechanism in the reconfiguration of class relations in this field. By conceptualising parenthood as a field, that is a social world with specific stakes and rules, this study suggests that residential decisions and strategies developed by different middle‐class households do not solely depend on their class habitus, but also on gendered positions and dispositions in respect to division of labour, child care and school choice. Drawing on interview data from London and Amsterdam, this study re‐addresses the issue of middle–class time‐space trajectories at a specific period in the life course. We contend that the middle classes are not just differentiated by various orientations of capital (economic versus cultural) but that interaction of class and gender is also key for understanding practices of the middle classes as they enter the field of parenthood. These practices are strongly influenced by labour market and welfare regimes (as the Netherlands/England comparison makes clear). In the new field of parenthood the work of realigning class habitus (through social reproduction) is highly gendered, but to different degrees that are made evident in the different neighbourhood settings. In terms of urban space this points to the significance of the particular neighbourhood structure and opportunities of the city as a whole as well as a more active idea of the role of space in the particular working out of class and gender in specific neighbourhood contexts. Urban space is a situating framework and an active process in trajectories of social reproduction.